2005
DOI: 10.1111/j.1463-1318.2005.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of outcome from rubber band ligation of piles

Abstract: Most patients with piles of any degree can be safely managed by rubber band ligation, but return of symptoms in the long term affects more than half of patients treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 13 publications
1
20
0
3
Order By: Relevance
“…No major complications occurred after rubber band ligation in this study. These findings are supported by other researches (4,11,16). …”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…No major complications occurred after rubber band ligation in this study. These findings are supported by other researches (4,11,16). …”
Section: Discussionsupporting
confidence: 78%
“…Bernal et al reported a recurrence rate of 13.8% for 287 procedures (1) Longman et al reported that at first short follow-up, 84% of their patients were symptom-free. Long term follow up performed by questionnaire found that 44% of responders remained asymptomatic at a median of 46 months from banding (11). This difference is due to different grade of hemorrhoids and duration of follow up period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations